La leyenda del Mohån del municipio de Cogua, Cundinamarca como estrategia metodológica para incentivar a los niños de primera infancia el sentido de pertenencia (2020)
This monographic document presents the degree work carried out in the municipality of Cogua, Cundinamarca on the strategy of the Mohan’s Legends, as an educational method that seeks to encourage the sense of belonging of boys and girls, under a qualitative ethnographic research methodology, collecting information through specific resources such as interviews, photographs, among others, that allow giving information about the Coguan reality that not only presents a cultural loss, but also a confusion about the legends and culture of the different regions of Colombia with those of the municipality. As a result, there is a clear differentiation of the cultural own, the regional identity and at the same time an incentive to take care of the natural assets of the municipality in the way of its legends presenting to the students the different rounds, which describe who is the Mohan de Cogua. Moreover, these rounds are found striking even for parents, since it is carried out on with traditional rhythms such as the Creole rumba and the guabina, motivating them to publicize the morals that the Mohan’s legend of the region has to offer, through activities and interpretations that they themselves executed based on these.